Polysulfone composite material as well as preparation method and application thereof
By preparing polysulfone composite materials, the chemical bonding and micro-void structure of modified rubber particles and modified polysulfone are used to enhance impact resistance, and the transparency is improved by the dispersion effect of amphiphilic copolymers and hyperbranched polyglycerol, thus solving the problems of impact resistance and service life of the filter device.
Patent Information
- Application Number
- CN202511103449.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-07
- Publication Date
- 2025-11-11
AI Technical Summary
Existing reusable filtration devices are insufficient in terms of impact resistance and lifespan; metal materials are opaque while glass materials are fragile.
By preparing a polysulfone composite material, the chemical bonding and micro-void structure of modified rubber particles and modified polysulfone are used to enhance the impact resistance, while the transparency is improved by the dispersion effect of amphiphilic copolymer and hyperbranched polyglycerol.
The filter device has been enhanced in terms of impact resistance and service life, while maintaining a certain level of transparency to meet analytical requirements.
Smart Images

Figure BDA0005537636850000101 
Figure BDA0005537636850000111 
Figure BDA0005537636850000112
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials technology, specifically to a polysulfone composite material, its preparation method, and its application. Background Technology
[0002] Reusable filters are used for sterilization or analysis under vacuum or pressure conditions, and are currently generally made of glass or metal. While reusable metal filters offer advantages such as corrosion resistance, ease of cleaning, and long service life, the color and state of the contents cannot be seen through the filter, which is detrimental to analysis. Reusable glass filters, although stable and highly transparent, are easily broken by impact and have a shorter lifespan. Summary of the Invention
[0003] (1) Technical problems to be solved
[0004] The purpose of this invention is to provide a polysulfone composite material, its preparation method, and its application, which enhances the impact resistance of reusable filter devices and extends their service life.
[0005] (2) Technical solution
[0006] To achieve the above objectives, on the one hand, the present invention provides a polysulfone composite material, its preparation method and application, wherein the raw materials include, by weight, 80-85 parts of modified polysulfone, 10-15 parts of modified rubber particles, 1-3 parts of amphiphilic copolymer, and 1-3 parts of hyperbranched polyglycerol;
[0007] The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS.
[0008] The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
[0009] Furthermore, the preparation method of the modified polysulfone includes the following steps:
[0010] S11. Polysulfone particles are soaked in dichloromethane to obtain swollen polysulfone. The swollen polysulfone is added to fuming sulfuric acid, and the mixture is stirred under nitrogen for 4-5 hours to obtain a reaction solution.
[0011] S12. Add the reaction solution dropwise to ice water, adjust the pH to 7, centrifuge and filter, wash the solid with deionized water until the conductivity is <10μS / cm, freeze dry to obtain modified polysulfone.
[0012] Furthermore, the mass ratio of the polysulfone particles to dichloromethane is 1:13 to 14.
[0013] Furthermore, the preparation method of the modified SEBS includes the following steps:
[0014] S21. Add SEBS to xylene and stir until completely dissolved. Add glycidyl methacrylate and dicumyl peroxide. After purging with nitrogen to remove oxygen, continue purging with nitrogen and heat to 110°C. React in the dark for 5-6 hours to obtain the reaction solution.
[0015] S22. After the reaction solution is cooled, it is poured into methanol to precipitate, filtered, extracted with methanol using a Soxhlet extractor, and dried under vacuum to constant weight to obtain modified SEBS.
[0016] Furthermore, the mass ratio of SEBS, glycidyl methacrylate, and dicumyl peroxide is 200:18 to 20:1.
[0017] Furthermore, the method for preparing the modified rubber particles includes:
[0018] The emulsion obtained by crosslinking hydrogenated polyisoprene with peroxide was copolymerized with modified SEBS to form a core-shell structure, and then spray-dried to obtain modified rubber particles.
[0019] Furthermore, the method for preparing the emulsion obtained by peroxide crosslinking hydrogenated polyisoprene includes the following steps:
[0020] S31. After cutting the hydrogenated polyisoprene into small pieces, add it to toluene and stir until completely dissolved. Then add a toluene solution of dicumyl peroxide and stir in the dark to obtain the oil phase.
[0021] S32. Dissolve sodium dodecyl sulfate and nonylphenol polyoxyethylene ether in deionized water and stir until transparent to obtain an aqueous phase. Slowly pour the oil phase into the aqueous phase and homogenize under high pressure to obtain a primary emulsion.
[0022] S33. The primary emulsion is transferred to a reaction vessel, reacted under nitrogen protection, distilled under reduced pressure, and cooled to obtain a peroxide-crosslinked hydrogenated polyisoprene emulsion.
[0023] Furthermore, the mass ratio of the hydrogenated polyisoprene, dicumyl peroxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether is 10:0.5 to 2:2:1.
[0024] Based on the same inventive concept, in a second aspect, the present invention also provides a method for preparing a polysulfone composite material, applicable to the aforementioned polysulfone composite material, the preparation method comprising:
[0025] A polysulfone composite material is obtained by mixing and melting modified polysulfone, modified rubber particles, amphiphilic copolymer and hyperbranched polyglycerol in a twin-screw extruder and then extruding.
[0026] Based on the same inventive concept, in a third aspect, the present invention also provides an application of a polysulfone composite material, wherein the polysulfone composite material is used as the bottle body of a reusable filter device.
[0027] This invention utilizes a ring-opening reaction at high temperature between the sulfonic acid groups (-SO3H) of modified polysulfone and the epoxy groups (-CH2-CH(O)CH2) of modified SEBS in modified rubber particles to generate hydroxysulfonate bonds. The chemical reaction equation is: -SO3H+-CH2-CH(O)CH2→-SO2-O-CH2-CH(OH)-CH2-. The formed hydroxysulfonate bonds enhance the bonding force between the modified polysulfone and modified rubber particles in the composite material. The sulfonic acid groups of the modified polysulfone form a hydrogen bond network with the residual ester groups of the modified SEBS, further strengthening the bonding force between the two phases. Simultaneously, under external force, microvoids are generated around the modified rubber particles, inducing plastic deformation. When the polysulfone composite material is used as the bottle body of a reusable filter device, the chemical bonds and microvoids can significantly improve the impact strength of the composite material, enhance the drop resistance of the reusable filter device, and ensure that the bottle body retains its functional integrity after accidental drops, extending its service life.
[0028] The refractive index difference between modified rubber particles and modified polysulfone, as well as the aggregation of modified rubber particles, induces light scattering, thereby reducing the transmittance of the composite material and decreasing the transparency of the reusable filter, which is detrimental to the observation and analysis of the contents. The polyethylene glycol segment of the amphiphilic copolymer is hydrophilic and compatible with modified polysulfone, while the polystyrene segment is hydrophobic, anchoring the modified rubber particles, reducing the interfacial energy between the two phases, promoting the dispersion of modified rubber particles in the polysulfone composite material, reducing light scattering, and improving the transparency of the composite material. Hyperbranched polyglycerol has a highly branched spherical or ellipsoidal structure with densely distributed hydroxyl groups at the ends. The hydroxyl groups of hyperbranched polyglycerol form hydrogen bonds with the ether bonds of the polyethylene glycol segment of the amphiphilic copolymer, generating a "copolymer-hyperbranched polyglycerol" composite. Its branched structure utilizes steric hindrance to prevent rubber particles from approaching each other, allowing the hydrophobic segments of the amphiphilic copolymer to be more uniformly anchored on the surface of the nonpolar modified rubber particles, significantly improving the dispersion efficiency of the amphiphilic copolymer.
[0029] (3) Beneficial effects
[0030] Compared with the prior art, the beneficial effects of the present invention are:
[0031] 1. The binding force of the modified SEBS epoxy group and the modified polysulfone sulfonic acid group in the modified rubber particles is strengthened by forming hydroxysulfonate bonds. The micropores generated around the modified rubber particles under external force can greatly improve the impact strength of the composite material. When the polysulfone composite material is used as the bottle body of a reusable filter device, it enhances the impact resistance of the device and extends its service life.
[0032] 2. The hydrophilic segment of the amphiphilic polymer is compatible with the modified polysulfone, while the hydrophobic segment anchors the modified rubber particles, promoting the dispersion of the modified rubber particles in the polysulfone composite material, reducing light scattering, and improving the transparency of reusable filter devices.
[0033] 3. Hyperbranched polyglycerol and amphiphilic copolymers form a "copolymer-hyperbranched polyglycerol" composite. The steric hindrance of the branched structure prevents the modified rubber particles from getting close to each other, so that the hydrophobic segments of the amphiphilic copolymer are more uniformly anchored on the surface of the nonpolar phase modified rubber particles, which significantly improves the dispersion efficiency of the amphiphilic copolymer. Attached Figure Description Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0035] Example 1
[0036] This embodiment discloses a polysulfone composite material, its preparation method and application. The raw materials, by weight, include 82 parts of modified polysulfone, 15 parts of modified rubber particles, 2.5 parts of amphiphilic copolymer, and 1.5 parts of hyperbranched polyglycerol.
[0037] The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS.
[0038] The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
[0039] Furthermore, the preparation method of the modified polysulfone includes the following steps:
[0040] S11. Soak polysulfone particles in dichloromethane for 30-40 min, filter to obtain swollen polysulfone, add swollen polysulfone to fuming sulfuric acid, and stir under nitrogen at 25-30℃ for 4-5 h to obtain reaction solution;
[0041] S12. Add the reaction solution dropwise to ice water while stirring vigorously. Adjust the pH to 7 with 5% ammonia. After centrifugation, filter the solution and wash the solid with deionized water until the conductivity is <10 μS / cm. Freeze-dry to obtain modified polysulfone.
[0042] Furthermore, the mass ratio of the polysulfone particles to dichloromethane is 1:13 to 14.
[0043] Furthermore, the preparation method of the modified SEBS includes the following steps:
[0044] S21. Add SEBS to xylene and stir at 70-80℃ until completely dissolved. Add glycidyl methacrylate and dicumyl peroxide, purge with nitrogen to remove oxygen for 30 min, continue purging with nitrogen and raise the temperature to 110℃, and react in the dark for 5-6 h to obtain the reaction solution.
[0045] S22. After the reaction solution is cooled to 25°C, it is poured into methanol to precipitate, filtered, extracted with methanol by Soxhlet for 24 hours, and dried under vacuum at 50-60°C to constant weight to obtain modified SEBS.
[0046] Furthermore, the mass ratio of SEBS, glycidyl methacrylate, and dicumyl peroxide is 200:18 to 20:1.
[0047] Furthermore, the method for preparing the modified rubber particles includes:
[0048] The emulsion obtained by crosslinking hydrogenated polyisoprene with peroxide was copolymerized with modified SEBS at 80°C to form a core-shell structure, and then spray-dried to obtain modified rubber particles.
[0049] Furthermore, the method for preparing the emulsion obtained by peroxide crosslinking hydrogenated polyisoprene includes the following steps:
[0050] S31. After cutting the hydrogenated polyisoprene into small pieces, add it to toluene and stir at 55-60°C until completely dissolved. Then add the toluene solution of dicumyl peroxide and stir in the dark for 30-35 minutes to obtain the oil phase.
[0051] S32. Dissolve sodium dodecyl sulfate and nonylphenol polyoxyethylene ether in deionized water at 60°C and stir until transparent to obtain an aqueous phase. Slowly pour the oil phase into the aqueous phase and homogenize under high pressure to obtain a primary emulsion.
[0052] S33. Transfer the primary emulsion to a reaction vessel, heat it to 70-80°C under nitrogen protection, react for 4-5 hours, distill under reduced pressure, and cool to 25°C to obtain peroxide crosslinked hydrogenated polyisoprene emulsion.
[0053] Furthermore, the mass ratio of the hydrogenated polyisoprene, dicumyl peroxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether is 10:0.5 to 2:2:1.
[0054] Based on the same inventive concept, in a second aspect, the present invention also provides a method for preparing a polysulfone composite material, applicable to the aforementioned polysulfone composite material, the preparation method comprising:
[0055] A polysulfone composite material is obtained by mixing and melting modified polysulfone, modified rubber particles, amphiphilic copolymer and hyperbranched polyglycerol in a twin-screw extruder and then extruding.
[0056] Based on the same inventive concept, in a third aspect, the present invention also provides an application of a polysulfone composite material, wherein the polysulfone composite material is used as the bottle body of a reusable filter device.
[0057] Example 2
[0058] This embodiment discloses a polysulfone composite material, its preparation method and application. The raw materials include 80 parts of modified polysulfone, 10 parts of modified rubber particles, 1 part of amphiphilic copolymer, and 1 part of hyperbranched polyglycerol by weight.
[0059] The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS.
[0060] The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
[0061] The preparation methods for the modified polysulfone, modified SEBS, and modified rubber particles in this embodiment are the same as those in Example 1. The preparation method for a polysulfone composite material in this embodiment is also the same as that in Example 1.
[0062] Example 3
[0063] This embodiment discloses a polysulfone composite material, its preparation method and application. The raw materials include 85 parts of modified polysulfone, 15 parts of modified rubber particles, 3 parts of amphiphilic copolymer, and 3 parts of hyperbranched polyglycerol by weight.
[0064] The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS.
[0065] The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
[0066] The preparation methods for the modified polysulfone, modified SEBS, and modified rubber particles in this embodiment are the same as those in Example 1. The preparation method for a polysulfone composite material in this embodiment is also the same as that in Example 1.
[0067] Example 4
[0068] This embodiment discloses a polysulfone composite material, its preparation method and application. The raw materials include, by weight, 82.5 parts of modified polysulfone, 12.5 parts of modified rubber particles, 1.5 parts of amphiphilic copolymer, and 1.5 parts of hyperbranched polyglycerol.
[0069] The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS.
[0070] The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
[0071] The preparation methods for the modified polysulfone, modified SEBS, and modified rubber particles in this embodiment are the same as those in Example 1. The preparation method for a polysulfone composite material in this embodiment is also the same as that in Example 1.
[0072] Comparative Example 1
[0073] This embodiment discloses a polysulfone composite material, its preparation method and application. The raw materials, by weight, include 78 parts of modified polysulfone, 8 parts of modified rubber particles, 0.5 parts of amphiphilic copolymer, and 0.5 parts of hyperbranched polyglycerol.
[0074] The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS.
[0075] The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
[0076] The preparation methods for the modified polysulfone, modified SEBS, and modified rubber particles in this embodiment are the same as those in Example 1. The preparation method for a polysulfone composite material in this embodiment is also the same as that in Example 1.
[0077] Comparative Example 2
[0078] Based on Example 1, the difference from Example 1 is that in this comparative example, the polysulfone particles were not soaked in dichloromethane to swell during the preparation of the modified polysulfone.
[0079] Comparative Example 3
[0080] Based on Example 1, the difference from Example 1 is that the reaction time with fuming sulfuric acid in this comparative example is shortened to 2 hours when preparing modified polysulfone.
[0081] Comparative Example 4
[0082] Based on Example 1, the difference from Example 1 is that this comparative example does not react with fuming sulfuric acid during the preparation of modified polysulfone.
[0083] Comparative Example 5
[0084] Based on Example 1, the difference from Example 1 is that nitrogen was not introduced during the preparation of modified SEBS in this comparative example.
[0085] Comparative Example 6
[0086] Based on Example 1, but unlike Example 1, this comparative example does not add glycidyl methacrylate when preparing modified SEBS.
[0087] Comparative Example 7
[0088] Based on Example 1, but unlike Example 1, this comparative example uses unmodified polysulfone.
[0089] Comparative Example 8
[0090] Based on Example 1, but unlike Example 1, this comparative example uses unmodified SEBS.
[0091] Comparative Example 9
[0092] Based on Example 1, but unlike Example 1, this comparative example does not include an amphiphilic copolymer.
[0093] Comparative Example 10
[0094] Based on Example 1, but unlike Example 1, this comparative example does not contain hyperbranched polyglycerol.
[0095] Comparative Example 11
[0096] Based on Example 1, but unlike Example 1, this comparative example does not include amphiphilic copolymers and hyperbranched polyglycerol.
[0097] Comparative Example 12
[0098] This comparative example is a blank group, which is Solvay Udel GF-120NT 20 pure polysulfone material.
[0099] Experimental Example 1
[0100] For drop resistance testing, the polysulfone composite materials obtained in Examples 1-4, Comparative Examples 1-8, and 12 were subjected to cantilever beam impact test, drop hammer impact test, and drop test, respectively; the results are shown in Table 1.
[0101] Cantilever beam impact test: A polysulfone composite material with a diameter of 63.5*12.7*3.2mm and a notch depth of 2.54mm was selected as the sample. The experiment was conducted at a temperature of 25±2℃ and a humidity of 50±5%RH. The pendulum energy was 2.75J and the impact velocity was 3.5m / s. The impact energy was recorded to obtain the impact strength.
[0102] Drop hammer impact test: A Φ100*2mm polysulfone composite disc was selected as the sample. The experiment was conducted at a temperature of 25±2℃ and a humidity of 50±5%RH. The punch was a Φ12.7mm hemispherical head with a mass of 5kg and a height of 0.5→2.0m (in 0.2m increments until failure). The failure energy was obtained.
[0103] Drop test: A reusable filter device made of polysulfone composite material was used as the sample. Drop tests were conducted at a temperature of 25±2℃ and a humidity of 50±5%RH at a distance of 1.2m from the ceramic tile floor to obtain the number of drops that caused the bottle to crack.
[0104] Table 1. Impact resistance test of polysulfone composite materials
[0105]
[0106]
[0107] Table 1 shows the results of cantilever beam impact test, drop hammer impact test, and drop test for each test group. In the polysulfone composites of Examples 1-4 and Comparative Examples 1, 2, 3, and 5, the epoxy groups of modified SEBS and the sulfonic acid groups of modified polysulfone form hydroxysulfonate bonds, which strengthen the bonding force between the modified rubber particles and the modified polysulfone phase. Under the action of external force, micro-voids are generated around the modified rubber particles, which can improve the impact strength of the composite material. Therefore, the impact strength, failure energy, and number of drops that cause bottle cracking of Examples 1-4 and Comparative Examples 1, 2, 3, and 5 are significantly higher than those of Comparative Examples 4, 6, 7, 8, and 12. Among them, Example 1 has the best drop resistance.
[0108] Experimental Example 2
[0109] Transparency testing was conducted on the polysulfone composite materials obtained in Examples 1-4 and Comparative Examples 1, 9, 10, and 11, including light transmittance and haze tests. The results are shown in Table 2.
[0110] Table 2 Transparency Testing of Polysulfone Composites
[0111]
[0112]
[0113] Table 2 shows the results of transmittance and haze tests for each experimental group. Comparative Example 12, being pure polysulfone material, exhibited the highest transparency. Comparative Example 11, without the addition of amphiphilic copolymer and hyperbranched polyglycerol, showed the lowest transmittance, highest haze, and lowest transparency due to the aggregation of modified rubber particles affecting light scattering. Comparative Example 10, with the addition of amphiphilic copolymer, benefited from the compatibility of the hydrophilic segment with the modified polysulfone and the anchoring of the modified rubber particles by the hydrophobic segment, promoting dispersion of the modified rubber particles in the polysulfone composite material, reducing light scattering, and improving transparency. Comparative Example 9, with the addition of hyperbranched polyglycerol, utilized steric hindrance to hinder the aggregation of modified rubber particles, thus improving transparency. Examples 1-4 and Comparative Example 1, with the addition of amphiphilic copolymer and hyperbranched polyglycerol, significantly improved the transparency of the polysulfone composite material through the dispersion of the amphiphilic copolymer and the co-dispersing effect of the hyperbranched polyglycerol. Among these, Example 1 showed the best effect, most closely resembling the transmittance and haze of pure polysulfone material.
[0114] Finally, it should be noted that although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A polysulfone composite material, characterized in that, The raw materials, by weight, include 80-85 parts of modified polysulfone, 10-15 parts of modified rubber particles, 1-3 parts of amphiphilic copolymer, and 1-3 parts of hyperbranched polyglycerol; The modified rubber particles comprise a solid-liquid composite; the liquid is an emulsion obtained by peroxide crosslinking hydrogenated polyisoprene; the solid is modified SEBS. The epoxy groups of the modified SEBS react with the sulfonic acid groups of the modified polysulfone to form hydroxysulfonate bonds; the amphiphilic copolymer includes a polystyrene-b-polyethylene glycol block copolymer.
2. The polysulfone composite material according to claim 1, characterized in that, The preparation method of the modified polysulfone includes the following steps: S11. Polysulfone particles are soaked in dichloromethane to obtain swollen polysulfone. The swollen polysulfone is added to fuming sulfuric acid, and the mixture is stirred under nitrogen for 4-5 hours to obtain a reaction solution. S12. Add the reaction solution dropwise to ice water, adjust the pH to 7, centrifuge and filter, wash the solid with deionized water until the conductivity is <10μS / cm, freeze dry to obtain modified polysulfone.
3. The polysulfone composite material according to claim 2, characterized in that, The mass ratio of the polysulfone particles to dichloromethane is 1:13-14.
4. A polysulfone composite material according to claim 1, characterized in that, The preparation method of the modified SEBS includes the following steps: S21. Add SEBS to xylene and stir until completely dissolved. Add glycidyl methacrylate and dicumyl peroxide. After purging with nitrogen to remove oxygen, continue purging with nitrogen and heat to 110°C. React in the dark for 5-6 hours to obtain the reaction solution. S22. After the reaction solution is cooled, it is poured into methanol to precipitate, filtered, extracted with methanol using a Soxhlet extractor, and dried under vacuum to constant weight to obtain modified SEBS.
5. A polysulfone composite material according to claim 4, characterized in that, The mass ratio of SEBS, glycidyl methacrylate, and dicumyl peroxide is 200:18 to 20:
1.
6. A polysulfone composite material according to claim 1, characterized in that, The method for preparing the modified rubber particles includes: The emulsion obtained by crosslinking hydrogenated polyisoprene with peroxide was copolymerized with modified SEBS to form a core-shell structure, and then spray-dried to obtain modified rubber particles.
7. A polysulfone composite material according to claim 1, characterized in that, The method for preparing the emulsion obtained by peroxide crosslinking hydrogenated polyisoprene includes the following steps: S31. After cutting the hydrogenated polyisoprene into small pieces, add it to toluene and stir until completely dissolved. Then add a toluene solution of dicumyl peroxide and stir in the dark to obtain the oil phase. S32. Dissolve sodium dodecyl sulfate and nonylphenol polyoxyethylene ether in deionized water and stir until transparent to obtain an aqueous phase. Slowly pour the oil phase into the aqueous phase and homogenize under high pressure to obtain a primary emulsion. S33. The primary emulsion is transferred to a reaction vessel, reacted under nitrogen protection, distilled under reduced pressure, and cooled to obtain a peroxide-crosslinked hydrogenated polyisoprene emulsion.
8. A polysulfone composite material according to claim 7, characterized in that, The mass ratio of hydrogenated polyisoprene, dicumyl peroxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether is 10:0.5 to 2:2:
1.
9. A method for preparing a polysulfone composite material, applied to the preparation of the polysulfone composite material as described in any one of claims 1 to 8, characterized in that, The preparation method includes: A polysulfone composite material is obtained by mixing and melting modified polysulfone, modified rubber particles, amphiphilic copolymer and hyperbranched polyglycerol in a twin-screw extruder and then extruding.
10. An application of a polysulfone composite material, characterized in that, The polysulfone composite material according to any one of claims 1-8 is used as the bottle body of a reusable filtration device.
Citation Information
Patent Citations
Alloy of polysulfone resin and semi-aromatic nylon and preparation method thereof
CN103382305A
High-toughness polyethersulfone resin and preparation method thereof
CN113956661A
Polysulfone composite material for extremely-high-temperature-resistant safety helmet as well as preparation method and application of polysulfone composite material
CN119264663A
Polymer composition
EP0133357A2